2006
DOI: 10.1186/1471-2407-6-181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 decreases breast cancer cell motility, invasion and matrix metalloproteinase expression

Abstract: Background: Cyclooxygenase (COX) is the rate-limiting enzyme that catalyzes the formation of prostaglandins. The inducible isoform of COX (COX-2) is highly expressed in aggressive metastatic breast cancers and may play a critical role in cancer progression (i.e. growth and metastasis). However, the exact mechanism(s) for COX-2-enhanced metastasis has yet to be clearly defined. It is well established that one of the direct results of COX-2 action is increased prostaglandin production, especially prostaglandin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 46 publications
5
109
0
2
Order By: Relevance
“…Recently, we found that COX-1 and COX-2 inhibitors reduced cell viability, MMP-2 and MMP-9 activities, and in vitro invasion of primary and metastatic HNSCC cells (Koontongkaew et al, 2010). Our findings are consistent with other studies that demonstrated the inhibitory effects of COX inhibitors on MMP activities in breast (Larkins et al, 2006), prostate (Attiga et al, 2000), colon (Ishizaki et al, 2006) and lung cancer cells (Karna & Palka, 2002). Regarding the role of COX-2 in the metastasis and invasion of HNSCC cells, the precise mechanism remains obscure, but a decrease of COX-2 dependent PGE 2 may downregulate MMP production through PGE 2 receptors (Dohadwala et al, 2002).…”
Section: Cox and Tumor Invasionsupporting
confidence: 92%
“…Recently, we found that COX-1 and COX-2 inhibitors reduced cell viability, MMP-2 and MMP-9 activities, and in vitro invasion of primary and metastatic HNSCC cells (Koontongkaew et al, 2010). Our findings are consistent with other studies that demonstrated the inhibitory effects of COX inhibitors on MMP activities in breast (Larkins et al, 2006), prostate (Attiga et al, 2000), colon (Ishizaki et al, 2006) and lung cancer cells (Karna & Palka, 2002). Regarding the role of COX-2 in the metastasis and invasion of HNSCC cells, the precise mechanism remains obscure, but a decrease of COX-2 dependent PGE 2 may downregulate MMP production through PGE 2 receptors (Dohadwala et al, 2002).…”
Section: Cox and Tumor Invasionsupporting
confidence: 92%
“…High COX-2 expression in breast tumors has been correlated with poor survival, distant metastasis and lower local-regional control of disease [2,3]. Ectopic expression of COX-2 in breast cancer cell lines was found to increase the production of prostaglandin E 2 (PGE 2 ) and interleukin-8 (IL-8), which are essential to COX-2-induced breast cancer invasion [5][6][7]. However, which downstream factors are inhibited by the COX-2/ PGE 2 /IL-8-mediated pathway to induce breast cancer cell invasion are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Her-2/Neu is now widely used by clinicians as a biomarker of poor prognosis and metastasis for patients with invasive breast cancer [167] . Molecular studies of breast cancer tissues have demonstrated that high levels of COX-2 and PGE-2 are correlated with amplified Her-2/Neu expression and increased activity of MMP [168,169] . The MMP are proteolytic enzymes that degrade basement membranes and are thus associated with tumor invasiveness, metastasis, and poor survival.…”
mentioning
confidence: 99%